2013
DOI: 10.1371/journal.pone.0074902
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multimodal Community Intervention Program to Prevent Suicide and Suicide Attempts: A Quasi-Experimental Study

Abstract: BackgroundMultilevel and multimodal interventions have been suggested for suicide prevention. However, few studies have reported the outcomes of such interventions for suicidal behaviours.MethodsWe examined the effectiveness of a community-based multimodal intervention for suicide prevention in rural areas with high suicide rates, compared with a parallel prevention-as-usual control group, covering a total of 631,133 persons. The effectiveness was also examined in highly populated areas near metropolitan citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 17 publications
2
41
0
2
Order By: Relevance
“…The national suicide‐prevention strategy should explore a standard package of programs to guide planning, implementation, and evaluation of the suicide‐prevention efforts with a sustained workforce among local authorities. We should note that the NOCOMIT‐J study, which has employed a package of suicide‐prevention programs in Japan from July 2006 to December 2009, reduced suicide rates in a rural area . The present study also indicated a positive association between a smaller population size and the establishment of a community network for suicide prevention.…”
Section: Discussionsupporting
confidence: 62%
“…The national suicide‐prevention strategy should explore a standard package of programs to guide planning, implementation, and evaluation of the suicide‐prevention efforts with a sustained workforce among local authorities. We should note that the NOCOMIT‐J study, which has employed a package of suicide‐prevention programs in Japan from July 2006 to December 2009, reduced suicide rates in a rural area . The present study also indicated a positive association between a smaller population size and the establishment of a community network for suicide prevention.…”
Section: Discussionsupporting
confidence: 62%
“…A recent study reports on a community-based multimodal intervention for suicide prevention in rural areas with high suicide rates in Japan. 30 As described in the revised GPSP of 2012, Japan's suicide prevention strategy should enhance evaluation and monitoring schemes.…”
Section: Resultsmentioning
confidence: 99%
“…These measures consisted of mass education campaigns, expanded mental health screening, and improved training of health professionals in crisis intervention and postvention [40,41]. Ono et al evaluated the effectiveness of a community-based multimodal intervention for suicide prevention in Japan, and reported that the intervention was effective in rural areas, but not in highly populated areas [42]. One suggested reason was that adherence to the program in densely populated areas was relatively low, pointing to the challenges of implementing the intervention in urban areas.…”
Section: Findings In Relation To Previous Researchmentioning
confidence: 99%